Cosmic ray north-south anisotropy 1961 - 1983 - Pomerantz, M. A.; Bieber, J. W. (1985)
Measurements from neutron monitors in Thule (Greenland) and McMurdo (Antarctica) were used to determine yearly values of the cosmic ray north-south anisotropy over the period 1961-1983. The results strongly suggest that superposed upon the mean anisotropy of 0.05% is a solar cycle variation of amplitude 0.03%. No evidence for a dependence of the anisotropy upon polarity of the solar poloidal magnetic field is found.